2022
DOI: 10.1177/20494637221092907
|View full text |Cite
|
Sign up to set email alerts
|

The core minimum dataset for measuring pain outcomes in pain services across Scotland. Developing and testing a brief multi-dimensional questionnaire

Abstract: Background: There is currently no agreed minimum dataset to inform specialist chronic pain service provision. We aimed to develop a Core Minimum Dataset (CMD) for pain services in Scotland and perform preliminary analysis to evaluate its psychometric properties in adults with chronic pain. Methods: The questionnaire was developed following a review of existing relevant data collection instruments and national consultation. The CMD questionnaire was completed alongside a routine pre-clinic questionnaire by pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Adequate and comprehensive data such as Big Data may contribute to improving the quality of previously acquired minimal datasets ( 13 ). Understanding which ontological approach and related data elements ( 14 ) would be more suitable for data sharing could facilitate the study of behavioural patterns appearing in social networks and the creation of digital citizen labs ( 15 ) where open discussions may foster public engagement on an important topic.…”
Section: Open Data For the Advancement Of Chronic Pain Researchmentioning
confidence: 99%
“…Adequate and comprehensive data such as Big Data may contribute to improving the quality of previously acquired minimal datasets ( 13 ). Understanding which ontological approach and related data elements ( 14 ) would be more suitable for data sharing could facilitate the study of behavioural patterns appearing in social networks and the creation of digital citizen labs ( 15 ) where open discussions may foster public engagement on an important topic.…”
Section: Open Data For the Advancement Of Chronic Pain Researchmentioning
confidence: 99%
“…However, Moore et al 19 reported higher uptake for their group programme from more affluent areas in Glasgow. There is limited understanding of this aspect of service delivery across Scotland; collection of the Scottish Core minimum dataset 20 combined with analysis of demographics could be useful here.…”
mentioning
confidence: 99%
“…This extends from improving the quality and timeliness of pain management support, to reducing adverse effects and other harms of analgesics which are known to increase the burden on health care services, in all sectors. Outcome data, such as that described by Laskawska and colleagues 9 also in this issue, are going to be vital for assessing changes in analgesic stewardship and the burden of pain in our communities as analgesic stewardship initiatives spread across the UK and the rest of the world.…”
mentioning
confidence: 99%